Developing Multicultural Competence through Deep Learning: A Quasi-Experimental Study of Indonesian School Counselors - Nandang Budiman; Aam Imaddudin; Ibrahim Al Hakim; Yuli Nurmalasari; Eem Munawaroh; Yasinta Putri Khairunnisa; Christine Grace Yane Juwita (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study examines the effectiveness of deep learning-based training in strengthening multicultural competence and awareness of radicalism among Indonesian school counselors. Employing a quasi-experimental mixed-method design, the study involved 17 guidance and counseling teachers from secondary schools in Garut Regency, West Java. The three-week intervention integrated Socratic dialogue, experiential simulation, and structured cultural reflection. Quantitative data were collected using a pretest-posttest Radicalism Attitude Inventory, while qualitative data were obtained from reflective portfolios, interviews, focus group discussions, and observations. The paired-sample t-test revealed statistically significant improvement in counselors' radicalism awareness (p = 0.015, Cohen's d = 0.657), driven primarily by substantial gains in detecting overt radicalism indicators (Revolutionary dimension: p = 0.001, d = 1.03). Qualitative findings demonstrated transformative professional development, including increased cultural self-awareness, enhanced empathetic and dialogic counseling skills, greater sensitivity to subtle forms of intolerance, and improved readiness to implement preventive strategies in school contexts. Overall, the findings indicate that deep learning-based training facilitates professional transformation through iterative reflection and experiential learning, supporting its integration into counselor professional development programs focused on multicultural practice and radicalism prevention. Keywords: deep learning, mixed-method research, multicultural competence, radicalism prevention, school counselors